2023
DOI: 10.3390/ijms24087005
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Use of Mitochondrial Extracellular Vesicles as Biomarkers or Therapeutical Tools

Abstract: The mitochondria play a crucial role in cellular metabolism, reactive oxygen species (ROS) production, and apoptosis. Aberrant mitochondria can cause severe damage to the cells, which have established a tight quality control for the mitochondria. This process avoids the accumulation of damaged mitochondria and can lead to the release of mitochondrial constituents to the extracellular milieu through mitochondrial extracellular vesicles (MitoEVs). These MitoEVs carry mtDNA, rRNA, tRNA, and protein complexes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 133 publications
(165 reference statements)
0
5
0
Order By: Relevance
“…Mitochondria are also transported from donor cells via EVs [23] and enter the cytoplasm of the recipient cells through endocytosis or fusion [24]. Zhang et al found that EV-mediated mitochondrial transfer from human umbilical cord-derived mesenchymal stem cells to okadaic acid-treated SH-SY5Y cells, an in vitro model of Alzheimer's disease, reversed apoptotic signaling, improved cellular immune response, and reduced oxidative stress [25].…”
Section: Methods Of Mitochondrial Transplantation 21 Natural Mitochon...mentioning
confidence: 99%
“…Mitochondria are also transported from donor cells via EVs [23] and enter the cytoplasm of the recipient cells through endocytosis or fusion [24]. Zhang et al found that EV-mediated mitochondrial transfer from human umbilical cord-derived mesenchymal stem cells to okadaic acid-treated SH-SY5Y cells, an in vitro model of Alzheimer's disease, reversed apoptotic signaling, improved cellular immune response, and reduced oxidative stress [25].…”
Section: Methods Of Mitochondrial Transplantation 21 Natural Mitochon...mentioning
confidence: 99%
“…EVs can also transport mitochondrial enzymes, mitochondrial DNA, parts of the electron transport chain, mitochondrial fragments, and whole mitochondria ( 61 ). The role of these “mitoEVs” carry many implications for inflammatory pathways, which are tightly regulated by mitochondrial function ( 62 ).…”
Section: Potential Interactions Of Extracellular Vesicles and Immune ...mentioning
confidence: 99%
“…Delivery of whole mitochondria to macrophages via EVs also plays a critical role in macrophage polarization ( 63 ). Damaged mitochondria can be packaged into EVs and sent to neighboring cells for repair ( 61 ). For example, MSCs undergoing mitophagy package damaged mitochondria into EVs, which are delivered to neighboring macrophages that complete the process of mitophagy, resulting in enhanced OXPHOS and M2-like polarization ( 64 ).…”
Section: Potential Interactions Of Extracellular Vesicles and Immune ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Borrás et al [ 8 ] highlights the potential use of mitochondrial extracellular vesicles as biomarkers or therapeutic tools, suggesting their relevance to various conditions. Mitochondria play a critical role in cellular functions such as metabolism, ROS production, and apoptosis.…”
mentioning
confidence: 99%